Unveiling the Need of Synonym in Code Mixing in the Movie ‘Yowis Ben Finale’ - Dwi Putri Fatmawati; Dyah ‘Ainun Rohimah; Efazetta Fazafaza; Jaizah Nasywa; Teguh Sarosa (PRASASTI: Journal of Linguistics, 2024)
This study aims to analyze the internal, external, and factors that arise through the use of code-mixing by the players of the film "Yowis Ben Finale." Using a descriptive qualitative approach, this research method systematically analyzes factual information to accurately interpret the integration of Indonesian and Javanese in the film. Primary data were collected by observing the movie video and taking notes on the scripts containing code-mixing. In addition, secondary data were collected from several cited journals. The results highlight the significant interaction between Indonesian and Javanese, which enhances character depth and narrative richness. The multi-layered dynamics of code-mixing contribute to a nuanced depiction of cultural and linguistic diversity within the framework of the film. The findings reveal an interesting interplay between Indonesian and Javanese, which enriches the film's narrative and character interactions, thus enhancing its authenticity and appeal.